Penyuluhan Meningkatkan Pengetahuan Remaja Tentang Kesehatan Mata - Cicilia Wahju Djajanti; Paula Aprilia Sukmanto; Iriene Kusuma Wardhani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
At Lack of information is a risk factor for lack of knowledge on adolescents about the eye health. Phenomenon was obtained by adolescents in Kemala Bhayangkari 4 Waru High School had never received information about eye health. When they were asked didnâ€™t know how to keep eye health. The purpose of this study was to identify effect of counseling on the level of knowledge (know) of adolescents about eye health before and after counseling in Kemala Bhayangkari 4 Waru High School. Design of this study was Pre Experimental One Group Pre Post Test Design. Sample of this study was grade X students at SMA Kemala Bhayangkari 4 Waru which included as many as 58 inclusion criteria using simple random sampling techniques. Instrument used was a questionnaire. Data were analyzed using descriptive statistics proportion with results before giving counseling 45% of respondents had a lack of knowledge. After being given counseling more than 50% (65%) of respondents had a good level of knowledge. Wilcoxon test results showed value of Ï (0,000) <Î± (0.05), so H0 was rejected, meaning that there is an influence of counseling on the level of knowledge (know) of adolescents about eye health before and after counseling.